Citra Ibu Dalam Puisi “Pulang Ke Dapur Ibu” Karya Aan Mansyur Dan Lirik Lagu “Bertaut” Karya Nadin Amizah - Elpida Fathi Garwita; Assifa Atsna Hanifa (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This study aims to describe how the image of a mother is compared based on physical aspects, psychological aspects, and social aspects in poetry and song lyrics. The poem in question is